Work stress and job satisfaction among Malaysian antidrug professionals: the mediating role of coping strategies - Azam, Naqi Dahamat; Md Nordin, Noradilah; Rosnon, Mohd Roslan; Abu Talib, Mansor (2023)
Recent studies have suggested that coping strategies can mediate the relationship between work stress and job satisfaction in working adults. However, the role of coping strategies as a mediator on the relationships had not been proven, particularly among antidrug professionals in Malaysia. Thus, the purpose of this study was twofold. First, to examine the relationships between work stress and job satisfaction. Second, to investigate the mediating effect of coping strategies on the relationships. A total of 3,356 participants (69% males; aged between 21 and 59 years) completed an online survey that measured job satisfaction, control and avoidant coping strategies, and work stress. The results indicated that work stress was related to job satisfaction. Furthermore, the serial mediation test revealed that the relations between work stress and job satisfaction were mediated by both control and avoidant coping. The present study suggests that adopting positive-type coping strategies such as control coping can be effective in tackling stress at workplace, and indirectly contribute to job satisfaction.